Resilience Ecotourism in Papua Amid Covid 19 Pandemic - Dewi, Liliana (E-Journal of Tourism; Volume 7 Number 2 (September 2020), 2020)
Tourism destination is facing numerous crises caused by climate change, natural disaster, economic recession, instability political, internal turmoil and terrorism. These crises affect inbound tourism flows and consequently the tourism industry. New crisis as we know Covid 19 pandemic affecting many sectors, the most affected is the tourism industry. Purpose of this research was (1) to determine mitigation strategies of Ministry of Tourism and Creative Economy amid Covid 19 pandemic, (2) to learn the adaptation strategy of community ecotourism to survive amid Covid 19 pandemic and (3) to analyze the implication of Covid 19 epidemic on ecotourism destination resilience in Papua. The research was qualitative research with descriptive explanation, and data collections used interview, documentation, literature study. SWOT analysis method to analyze strength, weakness, opportunity and threat of resilience ecotourism in Papua. The procedure of data analysis techniques in this research used (1) data reduction, (2) presentation data, (3) conclusions. The result of this study showed there were three adaptation strategies (1) physically (2) economically, and (3) social. Covid 19 pandemic gives big implicated to the economic sector, social and culture sectors on ecotourism destination resilience. Cancellations of guest booking and travelling restriction impact on community ecotourism lifecycle. Meanwhile, other industries such as geography, demography, natural resources, politic and security were not implicated by Covid 19 pandemic. Keywords: ecotourism, resilience, Papua, Covid 19